A Study on Healthcare Delivery Acceptability through Mobile Phone among Rural Population - Ashwini LH; Balu PS; Javalkar, Sandhyarani (National Journal of Community Medicine, 2019)
Introduction: Mobile health has great potential to expand access and improve the quality of rural healthcare. Objective: Exploring the acceptability of mobile phones in healthcare interventions among rural populations of Davangere taluk. Methodology: A cross sectional study was conducted among 182 mobile phone users, residing in kukkuwada village, Davangere Taluk. Data collected by house to house survey using semi-structured, pretested, and pre-validated questionnaire. Results: The primary use of mobile phones among study subjects was to make or receive phone calls 182(100%). Text messaging was used by only 51(28%) of respondents. All the respondents were willing to receive health related information on their mobile phones. Out of 128(70.3%) respondents who preferred advice on vaccinations for their children 106(58.2%) preferred once in a month. 178(97.8%) were willing to make appointment with doctor via phone. Factors such as gender, literacy, employment and presence of chronic diseases affected preferences regarding mode of communication. Conclusion: Mobile phone as a mean of receiving health information and supporting healthcare through mobile health interventions is acceptable in rural India.